The Role of Leadership and Personality in Trust - Sitompul, Pandapotan; Munthe, Kornel (APPS Publications, 2021)
This study aims to investigate the role of leadership and personality in trust. This research uses a survey with a multiple regression analysis approach. The size of the sample is 105 respondents who were selected at simple random from a population of 145 populations using the Slovin formula who were at a low managerial level with work experience of more than five years and assigned to the plantation area were surveyed. The results of the study found that there is a direct positive influence of leadership on trust. Also, there is a direct positive influence of personality on trust. Additionally, there is a joint influence of leadership and personality on trust. Referring to these findings, the researcher can conclude that trust is positively influenced by leadership and personality. Therefore, to maintain trust, organizations must apply leadership and personality. Finally, it is concluded that leadership and personality must be considered in generating trust. To increase trust, it should be by increasing leadership, because the value of the coefficient of influence is greater than personality.